TAX BEHAVIOR OF ECONOMIC AGENTS: MULTIAGENT-BASED ANALYSIS - Акулова, Г. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The paper describes the multi-agent model of fiscal behavior of economic agents, which act as a jurisdiction and the taxpayers who differ in their behavioral characteristics and factors of production, of which they are carriers.